Winning Together : The Natural Resource Negotiation Playbook - Verdini Trejo, Bruno (Book collections on Project MUSE., 2017)
Strategies for transboundary natural resource management; winner of Harvard Law School's Raiffa Award for best research of the year in negotiation and conflict resolution.